The postcolonial sociology of love in Gandhi’s non-violent political culture of Satyagraha - Gianolla, Cristiano (Frontiers in Sociology, 2025)
Satyagraha is the philosophy of non-violent resistance and a critical constructivist approach—building on life experience and experimentation—to social action. It was delineated by M. K. Gandhi in the first half of the 20th century and characterized the anti-colonial struggle in India. It was also mobilized to overcome polarization between religious, social, and cultural groups in search of dialogue. Finally, Satyagraha included postcolonial provisions for a democratic system based on duty, empathy, and social love. Gandhi’s theory and social work combined a critique of individualism, state centralism, and representation in liberal democracy and the construction of a political culture based on social love from the community level. Gandhi projected a socio-political theory of democratization through cognitive-emotional liberation from heteronomous processes of subjectivation in favor of the self-construction of subjectivity. Satyagraha elaborates autonomy as individual and collective self-rule or swaraj. On the basis of critical autonomy, Satyagraha constructs interpersonal and intercultural dialogue and social governance outlined by “welfare for all” or sarvodaya, a duty-based approach to democratization. This article analyzes the love-centered philosophy of Satyagraha, exploring the relevance of its key conceptual constructs in relation to the mobilization of social and political emotions and investigating the way in which it produced a comprehensive political culture of social love. Non-violence (ahimsa) is the method based on the duty to achieve truth (satya), which prioritizes love and relational emotions over force and one-sided or principled reason. Satyagraha generates social dialogue, promotes liberation from the domination of possession and passion, as well as the achievement of (individual, social, and political) swaraj. Ahimsa was both the key to mobilizing the entire population from the bottom up, ensuring socio-political harmony in a prospective independence, and to building a political culture in which means and ends were prefiguratively aligned. Gandhi formulated an original, utopian, and thought-provoking political philosophy, which is subject to ambiguities and limitations, stimulating provocative reflections on empathy and social love.